Grouping Together to Fight Cancer: The Role of WeChat Groups on the Social Support and Self-Efficacy - Zhong, Fangqi; Pengpeng, Li; Qianru, Zhuo (Frontiers in Public Health, 2022)
With the increasing number of cancer survivors, the question of how to coexist with cancer has become more and more pressing. This research uses a mutual help WeChat group organized by cancer patients as the research field to observe the daily interactions of cancer patients, so as to improve understanding of how social media technology can help cancer patients in the treatment and recovery process. The study found that the WeChat group is the main source of health knowledge for the participating cancer patients, and that when compared to traditional web-based patient mutual aid communities, the WeChat group is a more timely, popular, continuous, and accurate source of information. Patients in the group can listen and respond to each other’s questions and worries, providing both an outlet for patients to vent their emotions and concerns and a source of recognition and encouragement. In addition, this study found that the WeChat mutual aid group improves patients' self-efficacy of disease on four levels: successful experience in curing patients, imitating patients' behavior, verbal persuasion, and emotional support.